The Community of Inquiry Framework in Contemporary Education : Emerging Research and Opportunities - Semingson, Peggy, author; Smith, Pete, 1961-, author; Anderson, Henry I., 1947-, author (Hershey, PA : IGI Global, 2018)
"This book contains a deeper examination of research on online learning using the Community of Inquiry (COI) framework integrated or overlaid with a big data approach--sprung from a series of conversations that took place amongst this book's authors across multiple collaborative projects"